2016
DOI: 10.1016/j.cct.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and study design for a phase I/IIa trial of anakinra in children with Kawasaki disease and early coronary artery abnormalities (the ANAKID trial)

Abstract: Background Although Kawasaki disease (KD) is the most common cause of acquired heart disease in children and may result in coronary artery aneurysms (CAA) with an attendant risk of myocardial infarction, there is no recommended therapy to halt progression of arterial wall damage and prevent aneurysm formation in the acute phase of the vasculitis. While intravenous immunoglobulin (IVIG) reduces the risk of CAA, up to 20% of KD patients are IVIG resistant and have a higher risk for developing CAA. The IL-1 pro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 51 publications
2
32
0
1
Order By: Relevance
“…This then led to clinical trials for the use of IL-1R (Anakinra) in children with KD and is currently in phase IIa of clinical trials [52]. …”
Section: Etiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…This then led to clinical trials for the use of IL-1R (Anakinra) in children with KD and is currently in phase IIa of clinical trials [52]. …”
Section: Etiopathogenesismentioning
confidence: 99%
“…Therefore, use of TNF-α blockers could be one of the therapeutic strategies in KD patients to prevent aneurysms formation and is undergoing clinical trials [17]. It has also been shown that nitric oxide (NO) production is increased in KD patients and goes down rapidly with IVIG treatment [52]. NO is known to maintain normal vascular tension.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A Phase IIa multicenter trial is aimed at assessing the efficacy and safety of anakinra in patients with KD who failed to respond to standard treatment (i.e., one infusion of 2 g/kg of IVIG) (clinicaltrials.gov NCT02390596). Another Phase II trial is intended to assess the safety and activity of anakinra in infants and children <2 years old with coronary artery abnormalities (clinicaltrials.gov NCT02179853) [95].…”
Section: Treatments Under Investigationmentioning
confidence: 99%
“…Eleven articles were not in English and were excluded. Restricting to meta-analysis or randomised controlled trials (RCTs), there were five published RCTs, two prospective RCTs with results awaited1 2 and two relevant meta-analyses (table 1). …”
Section: Searchmentioning
confidence: 99%